Application of Exploratory Factor Analysis to Identify Factors Affecting Parents' Interest in Choosing SMK 45 Lembang - Sabathino Bansole; Bobby W. Saputra (Riviera Publishing, 2024)
Vocational High School (SMK) is a form of formal education organized by the government or private sector which is equivalent to Senior High School / Madrasah Aliyah, where Vocational High School has specialization in certain fields or sciences. the purpose of this study is to identify all components that influence parents' interest in choosing SMK 45 Lembang, West Bandung Regency to send their children to school, by applying exploratory factor analysis (EFA). The approach method used in this research is quantitative method. This research focuses on the factors that influence parents' interest in choosing SMK 45 Lembang, West Bandung Regency, as a place of education for their children. This type of research is included in the type of exploratory research. The population in this study amounted to 1607 with a sample of 150. Based on data obtained from the official website of the Central Statistics Agency (BPS), it appears that the number of SMK students has increased every year. National data shows that in West Java Provinc e, with a total of 1,765 schools in the 2011/2011 academic year, it became 2,515 schools in the 2015/2016 academic year. Meanwhile, the number of students in the same academic year increased from 717,362 students to 903,343 students. There are many factors that drive parents' interest in choosing a particular vocational school for their children, including: school facilities, human resources, individual influence (family, friends), products, school performance, cost, learning process, employment opportunities, place/ location, availability of majors of interest, promotion, extracurricular activities, quality of graduates, opportunities to continue higher education.